1993
DOI: 10.1161/01.hyp.21.5.695
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endogenous angiotensin on the renovascular response to norepinephrine.

Abstract: The purpose of this study was to elucidate the role of endogenous angiotensin II in mediating the renovascular effects of renal adrenergic stimulation. Six conscious dogs instrumented for monitoring of renal blood flow were subjected to step increases every 10 minutes in the rate of norepinephrine infusion into the renal artery. Under control conditions, infusion of norepinephrine (10-40 ng/min per milliliter per minute of control renal blood flow) increased plasma renin activity and decreased renal blood flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, the decrease in cardiac output by almost 50% during pacing would be expected to produce a less than twofold increase in plasma ANG II concentration. Although not investigated in the present study, elevations in plasma levels of ANG II of this magnitude have very little or no effect on systemic or renal hemodynamics, sodium excretion, drinking, or neurohormonal activation in normal dogs (3,16,35,36,44). Furthermore, if sustained increments in plasma levels of ANG II on days 1-8 of pacing had contributed to the above responses, we would not have expected all of the measured responses during this initial period of pacing to be quantitatively comparable to those in paced dogs with a functional renin-angiotensin system, normal PRA under basal conditions, and possibly even episodic exacerbations in renin secretion and plasma levels of ANG II during periods of activity (28).…”
Section: Discussionmentioning
confidence: 68%
“…However, the decrease in cardiac output by almost 50% during pacing would be expected to produce a less than twofold increase in plasma ANG II concentration. Although not investigated in the present study, elevations in plasma levels of ANG II of this magnitude have very little or no effect on systemic or renal hemodynamics, sodium excretion, drinking, or neurohormonal activation in normal dogs (3,16,35,36,44). Furthermore, if sustained increments in plasma levels of ANG II on days 1-8 of pacing had contributed to the above responses, we would not have expected all of the measured responses during this initial period of pacing to be quantitatively comparable to those in paced dogs with a functional renin-angiotensin system, normal PRA under basal conditions, and possibly even episodic exacerbations in renin secretion and plasma levels of ANG II during periods of activity (28).…”
Section: Discussionmentioning
confidence: 68%
“…The RAS, one of the main controllers of systemic blood pressure, can contribute to systemic hypertension in humans by exaggerating vasopressor responses to drugs [30], nutrients [31], or exercise [32]. One study, using 3 days of water deprivation in pregnant rats, reported increments in fetal plasma sodium concentration and osmolality in association with increments in fetal liver angiotensinogen mRNA and plasma angiotensin I and angiotensin II levels [33•].…”
Section: Prenatal Exposure To Maternal Water Deprivation and The Renimentioning
confidence: 99%
“…Weaning the alpha‐adrenergic agents before vasopressin infusion was purposely attempted since the response to norepinephrine is substantially reduced in patients with chronic congestive failure, due to down‐regulation of receptors 22 . This weaning is also desirable to minimize the detrimental effects of prolonged norepinephrine infusion: a direct negative inotropic cardiac action due to up‐regulation of TNF‐α, 23 hepatic ischemia and hepatocellular dysfunction, 23 and renal ischemia due to enhanced adrenergic stimulation in the presence of chronically blocked renin‐angiotensin system 24 . None of the patients in this study developed complications related to vasopressin infusion.…”
Section: Discussionmentioning
confidence: 99%